Pharmacist-Driven Management of Chemotherapy Induced Nausea and Vomiting in Hospitalized Adult Oncology Patients. A Retrospective Comparative Study - Ramy Elshaboury; Kathleen Green (University of Minnesota Libraries Publishing, 2011)
Chemotherapy-induced nausea and vomiting (CINV) is a major adverse event associated with cancer treatments. There are clinical practice guidelines that assist practitioners in managing CINV. Many cancer centers develop protocols for physicians and pharmacists to guide prophylaxis and breakthrough treatments of CINV based on published guidelines. The purpose of this study was to evaluate the outcome differences between pharmacist and physician -driven management of CINV in adult hospitalized cancer patients in a large academic medical center. This is a single center retrospective chart review study. The primary outcome of the study was the number of breakthrough antiemetic doses needed throughout the hospitalization. A total of 106 adult patients receiving inpatient chemotherapy were reviewed for CINV management. Fifty-five patients (52%) were managed according to the pharmacist-driven protocol, and fifty-one patients (48%) were managed by the physician. There was no difference between the two groups in the primary outcome. Patients in the pharmacist-managed group needed 6.4 breakthrough antiemetic doses; whereas, patients in the physician managed group needed 5.9 doses throughout the hospital stay (P-value = 0.7). No difference was seen when results were adjusted for length of hospitalization. There was a difference in adherence to the institution CINV guidelines favoring the pharmacist-driven approach (85% versus 33%, P < 0.0001). In conclusion, pharmacist-run protocol for CINV management was as effective as the standard of care. Protocols that are based on practice guidelines may offer the advantage of care standardization and potential cost savings.   Type: Student Project